Rural experiences and resilience: the role of local and indigenous knowledge in flood management - Tanriverdi, Mustafa; Erbesler Ayasligil, Tulay (TAYLOR & FRANCIS LTD, 2026)
Floods are among the most significant natural hazards and are expected to affect both urban and rural areas increasingly under climate change. Engineering-based solutions alone have proven insufficient for addressing flood risks associated with extreme weather events. This study investigates how indigenous knowledge can be integrated with scientific approaches to improve understanding of flood-generating factors and support more inclusive flood management. Focusing on the D & uuml;zce Melen Basin in northwestern T & uuml;rkiye, the research incorporates the experiential knowledge of village heads from flood-prone rural communities. Data were collected through descriptive semi-structured interviews with 30 village heads and analyzed using thematic analysis. The findings identify eight main themes related to flood causes: climate and meteorology, hydrology and topography, socio-economic and behavioural factors, institutional practices and administrative structures, natural cycles and indigenous knowledge, forest and land use, settlement and construction, and infrastructure and river improvement. The study also examines local and academic experts' perceptions of the role of indigenous knowledge in flood management. Results indicate that local knowledge can complement scientific data, particularly in data-scarce rural areas, improving flood susceptibility assessment and supporting more context-specific risk reduction strategies. The study proposes a framework for integrating community-based knowledge into flood susceptibility analysis.
Keywords: Local/indigenous knowledge; flood; local community leaders; Melen Basin; DISASTER RISK REDUCTION; ADAPTATION; LANDSCAPE; Water Resources